2015
DOI: 10.1186/s12888-015-0655-y
|View full text |Cite
|
Sign up to set email alerts
|

Stress reactions after a patient suicide and their relations to the profile of mental health professionals

Abstract: BackgroundPatient suicide is a professional hazard for mental health professionals and an event likely to trigger stress reactions among them.This study aimed to identify typical profiles of professionals after a patient suicide to address the severity of stress reactions and its discriminant variables.MethodsMental health professionals (N = 666) working in institutional settings or private practice in the French-speaking part of Switzerland filled out a self-administered questionnaire including the IES-R (Imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…A patient’s suicide always has a huge impact on healthcare professionals, especially on those working in the area of mental health, affecting them both at the professional and the personal levels [ 20 ]. Indeed, it can increase awareness of the factors involved in suicide risk [ 21 ], although, on the other hand, being involved in the care of people at risk for suicide can also trigger rejection, fear, and high levels of stress [ 22 ]. In general, healthcare professionals are sufficiently educated about suicidal behavior, but still there are certain lacks and problems that hinder an effective approach to it [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…A patient’s suicide always has a huge impact on healthcare professionals, especially on those working in the area of mental health, affecting them both at the professional and the personal levels [ 20 ]. Indeed, it can increase awareness of the factors involved in suicide risk [ 21 ], although, on the other hand, being involved in the care of people at risk for suicide can also trigger rejection, fear, and high levels of stress [ 22 ]. In general, healthcare professionals are sufficiently educated about suicidal behavior, but still there are certain lacks and problems that hinder an effective approach to it [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The finding that MHPs also experienced the suicide as a relief needs to be discussed. There are several studies that have identified stress and different emotional responses in staff (Dransart, Gulfi, & Gutjahr, 2015 often very difficult to predict and is often followed by negative emotional reactions in nurses (Bohan & Doyle, 2008), such as feeling emotionally strained or in psychological pain (Hagen et al, 2017). This indicates the need for sufficient formal support to be able to regulate emotions and feelings when caring for these patients.…”
Section: Death As a Reliefmentioning
confidence: 99%
“…The negative impact of PUS is significantly associated with a closeness to the deceased, a high level of the professional-client relationship and a lack of support and training. Castelli Dransart et al (2015) notably reported that the lack of support in the aftermath was a risk factor for higher traumatic impact in the aftermath of PUS.…”
Section: Introductionmentioning
confidence: 99%
“…Postvention refers to the activities developed in the aftermath of a suicide to prevent negative health outcomes and facilitate recovery among the bereaved (Andriessen, 2009). Despite the growing evidence on the impact of PUS, the lack of institutional support in the aftermath has been widely documented (Ruskin et al, 2004;Castelli Dransart et al, 2015;Leaune et al, 2019a,b). Moreover, the literature on postvention programs dedicated to the support of health and social work professionals remains scarce.…”
Section: Introductionmentioning
confidence: 99%